Improving the Quality of Colonoscopy Bowel Preparation Using an Educational Video. (2013) - Prakash, Sateesh R; Verma, Siddharth; McGowan, John; Smith, Betsy E; Shroff, Anjali; Gibson, Gregory H; Cheng, Michael; Lowe, Douglas; Gopal, Kavitha; Mohanty, Smruti R
Abstract : Colonoscopy is the preferred modality for colon cancer screening. A successful colonoscopy requires proper bowel preparation. Adequate bowel preparation continues to remain a limiting factor. One hundred thirty-three patients scheduled for an outpatient colonoscopy were prospectively randomized in a single-blinded manner to video or nonvideo group. In addition to written bowel preparation instructions, patients in the video group viewed a brief instructional video. Quality of colon preparation was measured using the Ottawa Bowel Preparation Quality scale, while patient satisfaction with preparation was evaluated using a questionnaire. Statistical analyses were used to evaluate the impact of the instructional colonoscopy video. There were significant differences in the quality of colonoscopy preparation between the video and the nonvideo groups. Participants who watched the video had better preparation scores in the right colon (P = 0.0029), mid-colon (P = 0.0027), rectosigmoid (P = 0.0008), fluid content (P = 0.03) and aggregate score (median score 4 versus 5; P = 0.0002). There was no difference between the two groups with regard to patient satisfaction. Income, education level, sex, age and family history of colon cancer had no impact on quality of colonoscopy preparation or patient satisfaction. The addition of an instructional bowel preparation video significantly improved the quality of colon preparation.